Clearing the Air : A Tale of Three Cities - World Bank (World Bank, Washington, DC, 2020)
Air pollution presents an increasingly apparent challenge to health and development across the globe. Exposure to PM2.5 is a major health risk and worldwide, an estimated 4.13-5.39 million people died prematurely in 2017 from exposure to PM2.5 pollution. The health impacts of pollution also represent a heavy cost to the economy. Lost labor income due to fatal illness from PM2.5 pollution globally in 2017 was in the range of US$ 131-317 billion, equal in magnitude to about 0.1-0.3 percent of GDP. Countries appear to follow growth paths with different levels of pollution intensity, suggesting that policy decisions, investments, and technologies all have an important role to play in affecting the pollution intensity of growth, and that countries cannot simply grow their way out of pollution. The experiences of three cities – Mexico City, Beijing, and Delhi – offers some lessons on how countries can tackle the growing challenge of air pollution. Notably, there is no silver bullet, and air pollution will only be tackled through sustained political commitment. Information, incentives, and institutions are the three prongs of an effective air pollution management strategy for any country.